Dual sEH/COX-2 Inhibition Using PTUPB—A Promising Approach to Antiangiogenesis-Induced Nephrotoxicity - Jankiewicz, Wojciech K.; Barnett, Scott D.; Stavniichuk, Anna; Hwang, Sung Hee; Hammock, Bruce D.; Belayet, Jawad B.; Khan, A. H.; Imig, John D. (Frontiers in Pharmacology, 2021)
Kidney injury from antiangiogenic chemotherapy is a significant clinical challenge and we currently lack the ability to effectively treat it with pharmacological agents. Thus, we set out to investigate whether simultaneous soluble epoxide hydrolase (sEH) and cyclooxygenase-2 (COX-2) inhibition using a dual sEH/COX-2 inhibitor PTUPB could be an effective strategy for treating antiangiogenic therapy-induced kidney damage. We used a multikinase inhibitor, sorafenib, which is known to cause serious renal side effects. The drug was administered to male Sprague Dawley rats that were on a high-salt diet. Sorafenib was administered over the course of 56 days. The study included three experimental groups; (1) control group (naïve rats), (2) sorafenib group (rats treated with sorafenib only (20mg/kg/d p.o.)), and (3) sorafenib+PTUPB group (rats treated with sorafenib only for the initial 28 days and subsequently co-administered PTUPB (10mg/kg/d i.p.) from days 28 through 56). Blood pressure was measured every two weeks. After 28 days, sorafenib-treated rats developed hypertension (161 ± 4 mmHg). Over the remainder of the study, sorafenib resulted in a further elevation in blood pressure through day 56 (200 ± 7 mmHg). PTUPB treatment attenuated the sorafenib-induced blood pressure elevation and by day 56 blood pressure was 159 ± 4 mmHg. Urine was collected every two weeks for biochemical analysis. After 28 days, sorafenib rats developed pronounced proteinuria (9.7 ± 0.2 P/C), which intensified significantly (35.8 ± 3.5 P/C) by the end of day 56 compared with control (2.6 ± 0.4 P/C). PTUPB mitigated sorafenib-induced proteinuria and, by day 56, it reduced proteinuria by 73%. Plasma and kidney tissue were collected on day 56. Kidney histopathology revealed intratubular cast formation, interstitial fibrosis, glomerular injury, and glomerular nephrin loss at day 56 in sorafenib-treated rats. PTUPB treatment reduced histological features by 30 to 70% compared with the sorafenib-treated group and restored glomerular nephrin levels. Furthermore, PTUPB also acted on the glomerular permeability barrier by decreasing angiotensin-II-induced glomerular permeability to albumin. Finally, PTUPB improved in vitro the viability of human mesangial cells. Collectively, our data demonstrate the potential of using PTUPB or dual sEH/COX-2 inhibition as a therapeutic strategy against sorafenib-induced glomerular nephrotoxicity.